Host cell killing and bacterial conjugation require overlapping sets of genes within a 22-kb region of the Legionella pneumophila genome - Segal, Gil (The National Academy of Sciences, 1998)
A 22-kb DNA locus of Legionella pneumophila is described that contains 18 genes, 16 of which are required for macrophage killing (icm genes). In this paper two previously described icm loci were linked by the discovery of five genes located between the two loci. Four of the newly described genes are required for macrophage killing (icmMLKE) and one is dispensable. The 16 icm genes appeared to be organized as six individual genes (icmR, icmQ, icmG, icmC, icmD, and icmF), and four operons (icmTS, icmPO, icmMLKE, and icmJB). Four icm genes (icmP, icmO, icmL, and icmE) show significant sequence similarity to plasmid genes involved in conjugation, whereas the other icm genes were found not to bear any sequence similarity to database entries. We found that L. pneumophila can mediate plasmid DNA transfer at a frequency of 10(−3) to 10(−4) per donor. Strains containing null mutations in two icm genes (icmT and icmR) showed a severe reduction in conjugation frequency and macrophage killing. Strains containing an insertion in four other icm genes (icmF, icmE, icmC, and dotA) were shown to have a less severe defect in conjugation. Mutations in the other 11 icm genes had no effect on conjugation frequency. We currently do not know whether conjugation itself plays a role in macrophage killing. It is possible either that small plasmids can take advantage of an existing secretion system to be mobilized or that DNA transfer is required for human macrophage killing by L. pneumophila.